114 Neuro-critical care: a 4-year experience. Issue 6 (27th May 2022) - Brown, Rachel; Spillane, Jennifer; Howard, Leo; Radcliffe, Jeremy; Kullmann, Dimitri; Howard, Robin
Abstract : There is an increasing demand for specialist intensive care driven by the complexities associated with prolonged admission for patients with primary neurological disorders. Provision in the UK remains inad- equate and it is essential to establish clear guidelines for appropriate referral. We describe 354 patients admitted to the Neurological Critical Care Unit (NCCU) at Queen Square over 4 years (2016–2019) and reflect on changes in the pattern of care. 95 patients were admitted with neu- romuscular disorders, 79 vascular, 68 autoimmune, 27 primary CNS infection, 20 prolonged or refractory epilepsy. We note a relative increase in the numbers of patients and duration of admission for those with autoimmune disorders, refractory status epilepticus and vascular disease. Indications for admission continue to include the multidisciplinary management of coma, profound weakness, bulbar, ventilatory and autonomic failure, status epilepticus and systemic complications of neurological disorders. Recent trends in admissions and duration of stay reflect the role of neurological intensive care in supporting patients requiring immunomodulatory treatments, specialist epilepsy man- agement and radiological or surgical intervention for vascular disease. Limited provision of neurological ICU raises issues concerning appropriate allocation of resources between the care of common acute neurological disorders and specialist tertiary referral requiring prolonged admission. robinhoward@nhs.net